A Hybrid Encryption Algorithm Based on DES and RSA In Bluetooth Communication (International Journal of Engineering and Computer Science, 2015)
The encryption algorithm employed by the Bluetooth to protect the confidentiality of data during transport between two or more devices is a 128-bit symmetric stream cipher called E0. It may be broken under certain conditions with the time complexity O(264 ).To enhance the security of data transmission in algorithm based on Data Encryption Standard (DES) and Rivets Shamir Adelman (RSA) is proposed